Penis wound by scorpion sting - Garcia, Adriano Scaff; Freitas, Danielo Garcia de; Freitas Filho, Osvaldo de (São Paulo Medical Journal, 1999)
CONTEXT: The majority of scorpion stings are oligosymptomatic, occurring mainly on the hands and feet. Fatality is rare. CASE REPORT: A 33-year old man suffered a severe sting on his penis from a scorpion of the species Tytius trivittatus. Alcohol and salt were used without success in an effort to relieve pain. Medical assistance was sought 4 hours after the event, at which time diffuse erythema, edema and punctiform injury on the glans penis were observed, with no systemic manifestation. Intravenous meperidine was administered with immediate relief of the pain. The local signs disappeared within 48 hours, with the patient remaining asymptomatic.